2010
DOI: 10.4061/2010/470695
|View full text |Cite
|
Sign up to set email alerts
|

Fc RIIA Genotypes and Its Association with Anti-C1q Autoantibodies in Lupus Nephritis (LN) Patients from Western India

Abstract: To identify Fc γ RIIA genotypes in Systemic Lupus Erythematosus (SLE) patients and their association with anti-C1q antibodies. Methods. Fc γ RIIA genotyping was done in eighty Indian SLE patients and eighty healthy controls using allele-specific PCR. Anti-C1q antibodies were measured by ELISA. Results. LN patients showed higher SLEDAI (6–32) as compared to SLE patients without renal manifestations and had SLEDAI between 6–23. Fc γ RIIA polymorphic frequency in SLE patients was R131/H131 (67.5%), R131/R131 (20%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…[172127] Our study showed a slightly higher incidence of anti-C1q antibodies (60%) in LN patients compared to non-LN patients (53.3%). This finding was similar to the studies reported by Zang et al .…”
Section: Discussionmentioning
confidence: 72%
“…[172127] Our study showed a slightly higher incidence of anti-C1q antibodies (60%) in LN patients compared to non-LN patients (53.3%). This finding was similar to the studies reported by Zang et al .…”
Section: Discussionmentioning
confidence: 72%